Nanofluid properties for forced convection heat transfer :a review - Darabi, Mohsen; Naeimi, Reza; Mohammadiun, Hamid; Mortazavi, Saeed (International Journal of Scientific World, 2015)
The thermal conductivity of nanofluids depends on various parameters, such as concentration, temperature, particle size, pH, shape, material, and possibly on the manufacturing process of the nanoparticles. Data on the viscosity of nanofluids, available in the literature, are very limited. Theoretical models for the determination of the thermal conductivity and viscosity of nanofluids have been pursued. Experiments with nanofluids indicate that they higher heat transfer coefficients than the base fluid. No significant increase in a pressure drop is reported with nanofluids, compared with values with the base fluid. However, the stability of nanofluids with regard to settlement/agglomeration, especially at higher concentrations, is still a problem for practical applications.